The craft of scientific writing - Alley, Michael (Springer, 1996)
The craft of scientific writing is designed to help scientists and engineers write about their work clearly and effectively. Using scores of examples from a wide variety of authors and disciplines (including such well-known figures as Einstein, Bohr, and Freud), the book demonstrates the difference between strong scientific writing and weak scientific writing. This book shows how to bring ideas across to the intended audience. In addition, it contains advice on how to start writing and how to revise drafts. Written for use as a text in courses on scientific writing, the book includes many useful suggestions about approaching a wide variety of writing tasks--from laboratory reports to grant proposals, from internal communications to press releases--as well as a concise guide to style and usage appropriate for scientific writing. The book is also useful for self-study and will be an important reference for all scientists and engineers who need to write about their work. Topics covered include deciding where to begin - structure: organizing your documents; providing depth, transitions, and emphasis - language: being precise, clear, and concise; being forthright, familiar, and fluid - illustration: making the right choices; creating the best designs - handling special situations - and actually sitting down to write: drafting, revising, finishing